The Effect of Interactivity and Visual Appeal on Impulse Buying of Fashion Products in TikTok Live Streaming: The Mediating Role of Perceived Usefulness and Perceived Enjoyment - Joya Damara Priyandarini; Tommy Christian Efrata (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
The rapid growth of live commerce in Indonesia has significantly transformed consumers’ online shopping behavior, particularly through TikTok Live. This study aims to examine the effect of interactivity and visual appeal on impulse buying of fashion products in TikTok live streaming, with perceived usefulness and perceived enjoyment serving as mediating variables. This research employs a quantitative approach using a survey method involving 200 respondents who have previously purchased fashion products through TikTok Live. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with the assistance of SmartPLS software. The results indicate that interactivity and visual appeal have a positive and significant effect on perceived usefulness and perceived enjoyment. Furthermore, perceived usefulness and perceived enjoyment are found to have a positive and significant influence on impulse buying. Mediation analysis reveals that perceived usefulness and perceived enjoyment partially mediate the relationship between interactivity, visual appeal, and impulse buying. These findings emphasize the strategic importance of interactive features and visual presentation in live streaming in shaping consumers’ cognitive and emotional experiences that ultimately stimulate impulsive purchasing behavior.